Long-term COVID-19 vaccine- and Omicron infection-induced humoral and cell-mediated immunity - Belik, Milja; Reinholm, Arttu; Kolehmainen, Pekka; Heroum, Jemna; Maljanen, Sari; Altan, Eda; Österlund, Pamela; Laine, Larissa; Ritvos, Olli; Pasternack, Arja; Naves, Rauno A.; Iakubovskaia, Alina; et al. (Frontiers in Immunology, 2024)
IntroductionMutations occurring in the spike (S) protein of SARS-CoV-2 enables the virus to evade COVID-19 vaccine- and infection-induced immunity.MethodsHere we provide a comprehensive analysis of humoral and cell-mediated immunity in 111 healthcare workers who received three or four vaccine doses and were followed up to 12 and 6 months, respectively, after the last vaccine dose. Omicron breakthrough infection occurred in 71% of the vaccinees, enabling evaluation of vaccine- and vaccine/infection-induced hybrid immunity.ResultsNeutralizing antibodies were the highest against the ancestral D614G and were sequentially reduced against the Omicron variants BA.2, BA.5 and XBB.1.5. S1-specific IgG and neutralizing antibody levels were significantly higher in infected than in uninfected vaccinees, and the fourth vaccine dose in combination with a breakthrough infection resulted in high neutralizing antibody levels against all variants. T cell-mediated immunity, instead, was well retained already after two vaccine doses, and was not significantly strengthened by additional booster vaccine doses or Omicron breakthrough infections.DiscussionWhile humoral immunity is sensitive to mutations in the S protein and thus declined rapidly, the cell-mediated immunity is durable to antigenic variation, which may explain the good efficacy of COVID-19 vaccines against a severe disease.